Dietary Inclusion of Seabuckthorn (Hippophae rhamnoides) Mitigates Foodborne Enteritis in Zebrafish Through the Gut-Liver Immune Axis - Li, Ming; Zhao, Xuyang; Xie, Jiayuan; Tong, Xinyu; Shan, Junwei; Shi, Mijuan; Wang, Guangxin; Ye, Weidong; Liu, Yuhang; Unger, Bruno Hamish; Cheng, Yingyin; Zhang, Wanting; et al. (Frontiers in Physiology, 2022)
To help prevent foodborne enteritis in aquaculture, several feed additives, such as herbal medicine, have been added to fish diets. Predictions of effective herb medicines for treating fish foodborne enteritis from key regulated DEGs (differentially expressed genes) in transcriptomic data can aid in the development of feed additives using the Traditional Chinese Medicine Integrated Database. Seabuckthorn has been assessed as a promising candidate for treating grass carp soybean-induced enteritis (SBMIE). In the present study, the SBMIE zebrafish model was used to assess seabuckthorn's therapeutic or preventative effects. The results showed that intestinal and hepatic inflammation was reduced when seabuckthorn was added, either pathologically (improved intestinal villi morphology, less oil-drops) or growth-related (body fat deposition). Moreover, seabuckthorn may block the intestinal p53 signaling pathway, while activating the PPAR signaling pathway and fatty acid metabolism in the liver. 16S rRNA gene sequencing results also indicated a significant increase in OTU numbers and skewed overlapping with the fish meal group following the addition of seabuckthorn. Additionally, there were signs of altered gut microbiota taxa composition, particularly for reduced TM7, Sphingomonas, and Shigella, following the addition of seabuckthorn. Hindgut imaging of fluorescent immune cells in SBMIE larvae revealed the immune regulatory mechanisms at the cellular level. Seabuckthorn may significantly inhibit the inflammatory gathering of neutrophils, macrophages, and mature T cells, as well as cellular protrusions’ formation. On the other hand, in larvae, seabuckthorn inhibited the inflammatory aggregation of lck+ T cells but not immature lymphocytes, indicating that it affected intestinal adaptive immunity. Although, seabuckthorn did not affect the distribution of intestinal CD4+ cells, the number of hepatic CD4+ cells were reduced in fish from the seabuckthorn supplementation group. Thus, the current data indicate that seabuckthorn may alleviate foodborne gut-liver symptoms by enhancing intestinal mucosal immunity and microbiota while simultaneously inhibiting hepatic adipose disposition, making it a potential additive for preventing fish foodborne gut-liver symptoms.